Chinese science in piano pedagogy: evaluating the chronicles of piano playing technique with taichi - Loo, Fung Ying; Loo, Fung Chiat (Elsevier, 2012)
This paper examines theories of taichi, and the application of this Eastern philosophical concept of movement in the aspect of piano playing technique. The theory of yin and yang, which is the philosophical backbone of all taichi movements, is examined in depth and its theory is employed in studying the traditional and modern approaches of piano playing. Selected components of taichi: balance between yin and yang, and the taichi diagram are found to give new insights in a piano pedagogical sense.